Alpha‐defensins: risk factor for thrombosis in COVID‐19 infection. (30th May 2021) - Abdeen, Suhair; Bdeir, Khalil; Abu‐Fanne, Rami; Maraga, Emad; Higazi, Mohamed; Khurram, Nigar; Feldman, Michael; Deshpande, Charuhas; Litzky, Leslie A.; Heyman, Samuel N.; Montone, Kathleen T.; Cines, Douglas B.; et al.
Summary: The inflammatory response to SARS/CoV‐2 (COVID‐19) infection may contribute to the risk of thromboembolic complications. α‐Defensins, antimicrobial peptides released from activated neutrophils, are anti‐fibrinolytic and prothrombotic in vitro and in mouse models. In this prospective study of 176 patients with COVID‐19 infection, we found that plasma levels of α‐defensins were elevated, tracked with disease progression/mortality or resolution and with plasma levels of interleukin‐6 (IL‐6) and D‐dimers. Immunohistochemistry revealed intense deposition of α‐defensins in lung vasculature and thrombi. IL‐6 stimulated the release of α‐defensins from neutrophils, thereby accelerating coagulation and inhibiting fibrinolysis in human blood, imitating the coagulation pattern in COVID‐19 patients. The procoagulant effect of IL‐6 was inhibited by colchicine, which blocks neutrophil degranulation. These studies describe a link between inflammation and the risk of thromboembolism, and they identify a potential new approach to mitigate this risk in patients with COVID‐19 and potentially in other inflammatory prothrombotic conditions.